CRISPR/Cas9 encouraged CAR-T cell immunotherapy reporting efficient and safe clinical results towards cancer. (2022) - Khan, Afreen; Sarkar, Esha
Highlights: Role of CRISPR/Cas9 gene engineering tool in CAR-T cell therapy. Generations of CARs based on the structural editing of T cell receptor (TCR). CRISPR/Cas9 enhanced CAR-T modifications to overcome challenges by knocking-in and knocking-out of genes. Explanation about the feasibility of allogenic CAR-T cells over autologous one. Pre-clinical and breakthrough Clinical trials done using CRISPR/Cas9 with their promising and successful outcomes with FDA approved CAR-T products in use for Cancer treatment. Abstract: CRISPR is a customized genome-editing tool that snips DNA in a simpler, cheaper and more precise way than any other gene editing tool. In recent years CRISPR/Cas has completely transformed an existing discipline of genetic engineering. This 'review' focuses on the generations and modifications in CAR-T as an advanced cancer therapeutic tool and CAR-T-approved products. It also highlights three path-breaking successful autologous and allogenic ex vivo CAR-T clinical trials in treating cancer using CRISPR/Cas9 which reported successful results despite the controversies regarding the safety of this technique. Outcomes from the first successful clinical trial showed the beneficial long-term effect on genetically modified T-cells in targeting cancer cells which opens the door for CRISPR to be the most preferred technique to help treat cancer and other diseases in the future. We searched the MEDLINE, EMBASE and PUBMED databases for original studies and meta-analysis on the use of CRISPR/Cas9 to edit T-cells until 2021. We finally selected 15 pre-clinical and 26 clinical studies for the review. Graphical abstract: Image, graphical abstract